Halogenation of A-frame μ-carbido complexes: synthesis of μ2-halocarbynes. Issue 12 (18th January 2019) - Barnett, Harrison J.; Hill, Anthony F.
Abstract : The new A-frame μ2 -carbido complexes [Rh2 (μ2 -C)X2 (μ2 -dppm)2 ] (X = Cl, Br; dppm = Ph2 PCH2 PPh2 ) react with PhICl2 or [pyH][Br3 ] to provide rare examples of μ2 -halocarbyne complexes [Rh2 (μ-CX)(μ-X)X4 (μ-dppm)2 ] (X = Cl, Br). Abstract : The reaction of [Rh2 (μ-C)Cl2 (PPh3 )4 ] with bis(diphenylphosphino)methane (dppm) affords the A-frame μ-carbido complex [Rh2 (μ-C)Cl2 (μ-dppm)2 ], halide metathesis of which provides [Rh2 (μ-C)Br2 (μ-dppm)2 ]. The reactions of the former with PhICl2 or the latter with [pyH][Br3 ] provide rare examples of μ2 -halocarbyne ligands in the complexes [Rh2 (μ-CX)(μ-X)X4 (μ-dppm)2 ] (X = Cl, Br).